2017
DOI: 10.1177/1073191116685806
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Dynamic Measure of Current Cognitive Reserve in a Longitudinally Assessed Sample of Healthy Older Adults: The Tasmanian Healthy Brain Project

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Associations between education and age are evident particularly in the attention and speed processing domains (Perry et al, 2017). In line with these findings, Summers et al (2017) found that 92.5% of individuals 50 years and older who had attended university for at least 12 months showed increased cognitive performance in domains that may be a proxy for cognitive reserve.…”
Section: Cognitive Reserve and Brain Connectivitysupporting
confidence: 65%
“…Associations between education and age are evident particularly in the attention and speed processing domains (Perry et al, 2017). In line with these findings, Summers et al (2017) found that 92.5% of individuals 50 years and older who had attended university for at least 12 months showed increased cognitive performance in domains that may be a proxy for cognitive reserve.…”
Section: Cognitive Reserve and Brain Connectivitysupporting
confidence: 65%
“…The present investigation found significant high levels of CFA fit indices at baseline and at follow-up. A Healthy Brain Project cohort found consistent results, demonstrating the stability of the longitudinal structure of the CFA in CR [ 16 ]. Moreover, this study applied measurement invariance, aiming to ensure reliable conclusions about real CR changes across time.…”
Section: Discussionmentioning
confidence: 85%
“…CFA model fit success may result from chance associations in the samples due to sampling error; analyses using completely independent samples could have increased the generalizability of the results (Brown, 2015). However, the use of overlapping samples is common in factor analyses (Flom et al, 2018; Foster & Mohler-Kuo, 2018; Olver et al, 2018), especially in multiwave studies (Castillo-Mayén et al, 2020; McKay et al, 2001; Summers et al, 2019). We believe the current CFA model results are likely to replicate because of the theoretical and empirical support for social and nonsocial anhedonia factors in other studies examining partially overlapping constructs (Chapman et al, 1976; Langvik & Borgen Austad, 2019).…”
Section: Discussionmentioning
confidence: 99%